2008
DOI: 10.1073/pnas.0802814105
|View full text |Cite
|
Sign up to set email alerts
|

The kinase domain of mitochondrial PINK1 faces the cytoplasm

Abstract: Mutations in PTEN-induced putative kinase 1 (PINK1) are a cause of autosomal recessive familial Parkinson's disease (PD). Efforts in deducing the PINK1 signaling pathway have been hindered by controversy around its subcellular and submitochondrial localization and the authenticity of its reported substrates. We show here that this mitochondrial protein exhibits a topology in which the kinase domain faces the cytoplasm and the N-terminal tail is inside the mitochondria. Although deletion of the transmembrane do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
259
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 287 publications
(285 citation statements)
references
References 40 publications
(84 reference statements)
24
259
2
Order By: Relevance
“…This study suggested that the N-terminus of PINK1 would be inserted in the OMM through the putative transmembrane domain (aa 94-110), with the kinase domain facing the cytosol. 13 Such a localization would argue against our hypothesis, as both N-and C-terminal domains of PINK1 are required to ensure a strong Beclin1 binding. Nevertheless, it is reasonable to speculate that a pool of PINK1-FL would not enter the OMM, but remain associated with mitochondria through anchoring proteins.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…This study suggested that the N-terminus of PINK1 would be inserted in the OMM through the putative transmembrane domain (aa 94-110), with the kinase domain facing the cytosol. 13 Such a localization would argue against our hypothesis, as both N-and C-terminal domains of PINK1 are required to ensure a strong Beclin1 binding. Nevertheless, it is reasonable to speculate that a pool of PINK1-FL would not enter the OMM, but remain associated with mitochondria through anchoring proteins.…”
Section: Discussionmentioning
confidence: 46%
“…9,10 The full-length PINK1 (PINK1-FL) is processed within mitochondria to generate two mature proteins; 4,11 all three isoforms localize both to the mitochondria and cytosol, their relative ratio being regulated by several factors. [10][11][12][13] Increasing data have demonstrated that absence of functional PINK1 induces abnormalities of mitochondrial morphology. 6,14,15 In several studies (mostly in Drosophila), PINK1 was shown to promote fission acting upstream of the Fis1-Drp1 machinery, and the mitochondrial phenotype observed in PINK1 knockout flies or silenced cells was associated to reduced fission.…”
mentioning
confidence: 99%
“…PINK1's kinase activity, but not mitochondrial localization, appears to be necessary for Parkin translocation (23)(24)(25). Because PINK1 can be found extramitochondrially (27)(28)(29)(30) and may directly phosphorylate Parkin (31,32), this may be a mechanism to stimulate its translocation. Alternatively, it may phosphorylate a Parkin substrate, e.g., Mfn, and thereby provide a recruitment signal.…”
Section: Discussionmentioning
confidence: 99%
“…Determining the genetic link between Sir2 and PINK1 may provide a key for decoding the signaling mechanism between mitochondria and Sir2. Moreover, PINK1 faces the cytoplasm in the outer membrane (Zhou et al, 2008), and cytosolic PINK1 can protect neurons from MPTP (Haque et al, 2008). Therefore, PINK1 may directly phosphorylate and activate Sir2 in the cytoplasm.…”
Section: Sir2 and Foxo As Novel Partners Of Pink1mentioning
confidence: 99%